2022
DOI: 10.1002/bmb.21684
|View full text |Cite
|
Sign up to set email alerts
|

Motivation, self‐efficacy, perception, curiosity, and barriers toward medical research among undergraduates in China

Abstract: Medical research is important to scientific progress and medical education.Institutions worldwide have sought to increase student involvement in research such as clinician-scientists training programs, while little is known about how medical undergraduates perceive research. A cross-sectional study was conducted in Chongqing Medical University, Chongqing, China, with first-fourth year undergraduates. An online, anonymous, and self-rating 5-point Likert questionnaire was conducted to investigate medical undergr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
(79 reference statements)
1
3
0
Order By: Relevance
“…The academic workload of Chinese medical students is shown to increase significantly in their second year and the lack of time is one of the most important barriers to participating in scientific research. [15][16][17] Our study, similar to previous studies, 18,19 shows that students are interested in extracurricular research but cannot participate because of time. In the future, providing students more time to engage in other activities, particularly scientific research, may require more effort.…”
Section: Discussionsupporting
confidence: 83%
“…The academic workload of Chinese medical students is shown to increase significantly in their second year and the lack of time is one of the most important barriers to participating in scientific research. [15][16][17] Our study, similar to previous studies, 18,19 shows that students are interested in extracurricular research but cannot participate because of time. In the future, providing students more time to engage in other activities, particularly scientific research, may require more effort.…”
Section: Discussionsupporting
confidence: 83%
“…However, there was lack of incorporating professional curricula into medical research for undergraduates in China. Even though they have strong interests and motivations, only a few undergraduates enrolled in research [10,12]. Most Chinese medical undergraduates participated in scienti c research through SRT spontaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Some differences in the proportion of students who selected academic stress were observed according to the year of study. “Based on a survey of our undergraduate students' research and a review of relevant literature, 7,9,10 we found that among freshmen, 90.4% chose academic stress, probably because at that initial level of tertiary study, students have not yet fully adapted to the pace of university studies and have not implemented a reasonable schedule because of the sudden transition from stressful high school life to relaxed university life. According to the actual situation of our school, we came up with the following results that the reason sophomores (91.2%) chose academic stress may be the large increase in the number of major courses and the need to prepare for CET 4 and 6, which can lead to a general perception of academic stress among sophomores.…”
Section: Discussionmentioning
confidence: 99%